Academic tourism through the perspective of Erasmus students - Quintela, Joana (2022)
This paper conducts a literature review on a topic that is still little explored, which is academic tourism, and explores through empirical research the perspectives of international students who have chosen the city of Porto to undertake Erasmus mobility. The main objective of the study is to better understand the motivations and factors that influence international student’s decisions to choose the location where they develop their mobility programs. An online survey was administrated and a total of 122 valid answers were collected. The data were analysed by descriptive and inference statistics. Results show that there are four main factors that influence this segment: quality and prestige of the universities; people's characteristics and hospitality; weather and landscape and being a fashionable destination.